Ninety-day hospital costs associated with prolonged air leak following lung resection. (31st August 2020) - Brunelli, Alessandro; Chapman, Kath; Pompili, Cecilia; Chaudhuri, Nilanjan; Kefaloyannis, Emmanuel; Milton, Richard; Tcherveniakov, Peter; Papagiannopoulos, Kostas; Mitchell, Thomas; Bassi, Vinod
Abstract: OBJECTIVES: Our goal was to assess the postoperative 90-day hospital costs of patients with prolonged air leak (PAL) including costs incurred after discharge from the initial index hospitalization. METHODS: We performed a retrospective analysis of 982 patients undergoing lobectomy (898) or segmentectomy (78) (April 2014–August 2018). A total of 167 operations were open, 780 were video-assisted thoracoscopic surgery and 28 were robotic. A PAL was defined as an air leak >5 days. The 90-day postoperative costs included all fixed and variable costs incurred during the 90 days following surgery. The postoperative costs of patients with and without PAL were compared. The independent association of PAL with postoperative 90-day costs was tested after adjustment for patient-related factors and other complications by a multivariable regression analysis. RESULTS: PAL occurred in 261 patients (27%). Their postoperative stay was 4 days longer than that of those without PAL (9.6 vs 5.7; P  < 0.0001). Compared to patients without PAL, those with PAL had 27% higher index postoperative costs [7354€, standard deviation (SD) 7646 vs 5759€, SD 7183, P  < 0.0001] and 40% higher 90-day postoperative costs (18 340€, SD 23 312 vs 13 102€, SD 10 264; P  < 0.0001). The relative postoperative costs (the difference between 90-day and index postoperative costs) were 50% higher in PAL patients compared to non-PAL patients ( P  < 0.0001) and accounted for 60% of the total 90-day costs. Multivariable regression analysis showed that PAL remained an independent factor associated with 90-day costs ( P  < 0.0001) along with the occurrence of other cardiopulmonary complications ( P  < 0.0001), male gender ( P  = 0.018), low carbon monoxide lung diffusion capacity ( P  = 0.043) and thoracotomy approach ( P  = 0.022). CONCLUSIONS: PAL is associated not only with increased index hospitalization costs but also with increased costs after discharge. Evaluation of the cost-effectiveness of measures to prevent air leaks should also include post-discharge costs. Abstract : Prolonged air leak (PAL) occurs in ∼8–10% of patients following lung resection [1].